Genome and catabolic subproteomes of the marine, nutritionally versatile, sulfate-reducing bacterium Desulfococcus multivorans DSM 2059. (December 2016) - Dörries, Marvin; Wöhlbrand, Lars; Kube, Michael; Reinhardt, Richard; Rabus, Ralf
Abstract Background Sulfate-reducing bacteria (SRB) are key players of the carbon- and sulfur-cycles in the sediments of the world's oceans. Habitat relevant SRBs are often members of theDesulfosarcina -Desulfococcus clade belonging to the deltaproteobacterial family ofDesulfobacteraceae . Despite this environmental recognition, their molecular (genome-based) physiology and their potential to contribute to organic carbon mineralization as well as to adapt to changing environmental conditions have been scarcely investigated. A metabolically versatile representative of this family isDesulfococcus multivorans that is able to completely oxidize (to CO2 ) a variety of organic acids, including fatty acids up to C14, as well as aromatic compounds. Results In this study the complete 4.46 Mbp and manually annotated genome of metabolically versatileDesulfococcus multivorans DSM 2059 is presented with particular emphasis on a proteomics-driven metabolic reconstruction. Proteomic profiling covered 17 substrate adaptation conditions (6 aromatic and 11 aliphatic compounds) and comprised 2D DIGE, shotgun proteomics and analysis of the membrane protein-enriched fractions. This comprehensive proteogenomic dataset allowed for reconstructing a metabolic network of degradation pathways and energy metabolism that consists of 170 proteins (154 detected; 91 % coverage). Peripheral degradation routes feed via central benzoyl-CoA, (modified) β-oxidation or methylmalonyl-CoA pathways into the Wood-Ljungdahl pathway for complete oxidation of acetyl-CoA to CO2 . Dissimilatory sulfate reduction is fueled by a complex electron transfer network composed of cytoplasmic components (e.g., electron transfer flavoproteins) and diverse membrane redox complexes (Dsr, Qmo, Hmc, Tmc, Qrc, Nuo and Rnf). Overall, a high degree of substrate-specific formation of catabolic enzymes was observed, while most complexes involved in electron transfer appeared to be constitutively formed. Conclusions A highly dynamic genome structure in combination with substrate-specifically formed catabolic subproteomes and a constitutive subproteome for energy metabolism and electron transfer appears to be a common trait ofDesulfobacteraceae members.